2011
DOI: 10.1007/s00431-011-1572-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 2-year etidronate treatment in a child with generalized arterial calcification of infancy

Abstract: High-dose bisphosphonate therapy may not be necessary for an extended period of time in children with GACI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 28 publications
1
54
1
1
Order By: Relevance
“…9 Thus, confirmation of a contribution of IEL/medial calcification to the occurrence of stroke might imply important novel options for stroke risk management.…”
Section: Discussionmentioning
confidence: 99%
“…9 Thus, confirmation of a contribution of IEL/medial calcification to the occurrence of stroke might imply important novel options for stroke risk management.…”
Section: Discussionmentioning
confidence: 99%
“…8 A limited number of case studies have reported on attempts to treat patients with GACI with oral and intravenous bisphosphonates. [21][22][23][24][25] There is no consensus, however, about the efficacy of bisphosphonates on the ectopic mineralization in these disorders. Some studies report apparent improvement, in some cases there has been very little, if any, effect, and in others bisphosphonate treatment has been accompanied by severe side effects.…”
Section: Discussionmentioning
confidence: 99%
“…20 Because PPi is relatively unstable in circulation and has a short half-life, administration of bisphosphonates, which are non-hydrolyzable PPi analogs, have been used to treat these patients with ectopic mineralization, including newborns or infants with GACI type 1 with ENPP1 mutations. [21][22][23][24][25] Careful analysis of these studies suggests improvements in some cases, no change in others, and even development of serious side effects in some patients. At the same time, recent demonstration of reduced PPi level in PXE patients suggested that bisphosphonates might be useful to treat ectopic calcification in patients with PXE and GACI type 2 due to ABCC6 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound showed diffusely hyperechoic abdominal aorta, common iliac arteries and renal arteries, generalized and diffuse calcification of the carotid arteries and increased echogenicity in the anterior cerebral and middle cerebral arteries, all with normal Doppler velocities. DNA sequencing of the ENPP1 gene showed a homozygous mutation in exon 14 at c.1412A>G, a mutation previously reported as disease-causing for IACI [1][2][3]. DNA analysis in each parent demonstrated heterozygosity for the same defect.…”
Section: Casementioning
confidence: 65%
“…IACI is inherited in an autosomal recessive pattern. Treatment with bisphosphonates, which are synthetic pyrophosphate analogues, has been proposed as a means of reducing arterial calcifications in IACI patients, but reported treatment regimens vary considerably both in terms of the specific bisphosphonate employed and the dose and duration of treatment [1][2][3].…”
Section: Introductionmentioning
confidence: 99%